What every engineer should know about practical CAD/CAM applications - Stark, John (What every engineer should know, 1986)
This authoritative book -- discussing CAD/CAM in detail from the user's rather than the vendor's point of view -- provides the valuable information engineers and managers need for optimal CAD/CAM implementation and use. It introduces CAD/CAM hardware and software, and demonstrates how to select a CAD/CAM solution for your company's specific requirements ... explains how to implement a CAD/CAM system, with special attention to training and education, and with useful checklists ... describes ongoing systems ... presents an informative overview of CAD/CAM's industrial use ... and details case studies of CAD/CAM applications, representing a broad range of companies throughout the world, in various industrial sectors, at different stages of CAD/CAM use. Complete with a glossary that clearly defines all CAD/CAM terminology, this essential reference source is mandatory reading for mechanical, manufacturing, automotive and aerospace engineers and managers; CAD/CAM system vendors; computer manufacturers; graduate-level courses in mechanical and manufacturing engineering, CAD/CAM, and computer science; and professional seminars in mechanical, manufacturing, and automotive engineering. Book jacket.